2017
DOI: 10.1186/s13054-017-1837-4
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable haptoglobin is associated with major adverse kidney events in critically ill burn patients

Abstract: BackgroundIntravascular haemolysis has been associated with acute kidney injury (AKI) in different clinical settings (cardiac surgery, sickle cell disease). Haemolysis occurs frequently in critically ill burn patients. The aim of this study was to assess the predictive value of haptoglobin at admission to predict major adverse kidney events (MAKE) and AKI in critically ill burn patients.MethodsWe conducted a retrospective, single-centre cohort study in a burn critical care unit in a tertiary centre, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Previous studies have also suggested the administration of haptoglobin as a therapeutic strategy against lethal sepsis and liver injury [38]. Major adverse kidney events, a complication common to severe sepsis, have been associated with haptoglobin levels below the detection limit of typical measurements in burn patients [39]. Hence, this would seem to suggest that the dip in HP protein observed, could be a useful new biomarker for sepsis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested the administration of haptoglobin as a therapeutic strategy against lethal sepsis and liver injury [38]. Major adverse kidney events, a complication common to severe sepsis, have been associated with haptoglobin levels below the detection limit of typical measurements in burn patients [39]. Hence, this would seem to suggest that the dip in HP protein observed, could be a useful new biomarker for sepsis progression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 ] A composite of renal outcomes, named major adverse kidney events (MAKE), has been endorsed by the National Institute of Diabetes and Digestive and Kidney Diseases clinical trials workgroup and used in recent studies. [ 16 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kubota et al [15] reported in their singlecenter retrospective study that haptoglobin provision during cardiovascular surgery was associated with a lower risk of post-operative AKI. More recently, Depret et al [22] reported that undetectable plasma haptoglobin was associated with major adverse kidney events in critically ill patients with burns. They provided a possible rationale for a biomarker-guided therapy using haptoglobin in patients with severe burns [22].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Depret et al [22] reported that undetectable plasma haptoglobin was associated with major adverse kidney events in critically ill patients with burns. They provided a possible rationale for a biomarker-guided therapy using haptoglobin in patients with severe burns [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation